Androgynous and undifferentiated differences in attributions of female success - Gackenbach, Jayne; Taylor, Melanie (My University, 1981)
Studies using unipolar models of sex role identity in conjunction with an attributional approach to female achievement prediction have found that androgynous women tend to consider ability to be a more feasible explanation for success than do either feminine or undifferentiated women. Androgynous, masculine, feminine and undifferentiated males and females (N=73) attributed reasons for female success to three types of cues: male-dominated, female-dominated, and exclusively female achievement areas. For external attributions, there were no differences among males, but feminine females were more likely than androgynous or masculine females to externally attribute female success. For internal attributions, feminine females were less likely than feminine males to use internal attributions across cues, while undifferentiated females were more likely than undifferentiated males to internally attribute across cues. Androgynous and masculine men and women reacted exactly opposite to each success activity. Results suggest that sex, sex role identity and situational variations occur in the prediction of female achievement behaviors.
Keywords: achievement; androgyny; attribution theory; individual psychology; locus of control; predictor variables; sex differences; sex role; success